2020
DOI: 10.1002/cctc.201901845
|View full text |Cite
|
Sign up to set email alerts
|

Eco‐Mn Ecocatalysts: Toolbox for Sustainable and Green Lewis Acid Catalysis and Oxidation Reactions

Abstract: Phytoextraction is one of the most promising phytotechnologies used to restore natural environments degraded by mining activities. In New Caledonia, a few plant species, which belong to the Grevillea genus, have the ability to extract Mn from soil and accumulate it in abundance (over 1 % of leaves dry weight). This review describes the use of Grevillea Mn‐accumulating plant species to produce the first bio‐sourced Mn catalysts, called Eco‐Mn catalysts. Extensive structural studies of Eco‐Mn catalysts have high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 125 publications
1
12
0
Order By: Relevance
“…As has been done previously with G. gillivrayi [ 31 ], the Mn-rich biomasses of P. stratiotes could be transformed into three classes of ecocatalysts ( Figure 1 ). A first class of ecocatalysts was obtained by grinding the air-dried leaves or roots into a 1.5 mm powder, which was then heated to 550 °C, leading to formation of Eco-MnOx-Ps.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…As has been done previously with G. gillivrayi [ 31 ], the Mn-rich biomasses of P. stratiotes could be transformed into three classes of ecocatalysts ( Figure 1 ). A first class of ecocatalysts was obtained by grinding the air-dried leaves or roots into a 1.5 mm powder, which was then heated to 550 °C, leading to formation of Eco-MnOx-Ps.…”
Section: Resultssupporting
confidence: 57%
“…The Grison group has shown that remediation phytotechnologies, such as phytoextraction [ 30 , 31 , 32 ], rhizofiltration [ 33 , 34 , 35 ] and biosorption [ 35 , 36 , 37 , 38 ], generate biomass rich in transition metals that can be turned into innovative catalysts, called ecocatalysts [ 39 , 40 , 41 ]. Using the concept of ecocatalysis, we advanced the aim that only natural or biosourced catalysts would be used for preparing the cyclic oxyterpenes.…”
Section: Introductionmentioning
confidence: 99%
“…This innovative methodology is based on the use of biomass derived from metal-hyperaccumulating plants, used in the phytoextraction of metal contaminated sites, for the preparation of polymetallic catalysts suitable for applications in organic synthesis. This concept was successfully applied for important transformations such as the Lewis and/or Brønsted acid-catalyzed reactions (Diels–Alder reaction, Friedel–Crafts reaction, multicomponent reactions, cascade reactions) [ 54 , 55 , 56 , 57 , 58 ]; coupling reactions (Suzuki, Heck, Sonogashira and Ulmann type reactions) [ 59 , 60 , 61 , 62 , 63 , 64 ]; reductions (aminoreduction, selective reduction of αβ-unsaturated carbonyl compounds, nitro- and halogeno arenes) [ 65 , 66 , 67 ]; oxidations (epoxidations, oxidative cleavage, oxidations of alcohols) [ 68 , 69 , 70 ]; and tandem reactions (tandem carbonyl-ene cyclization, synthesis of substituted pyridines and oxidative iodination of ketones) [ 71 , 72 , 73 ]. However, examples on the use of ecocatalysis for C-P bond formation have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, foliar Mn concentrations in Mn-hyperaccumulating species such as Grevillea meisneri can exceed 10,000 μg g −1 7 , 30 , 36 . Their Mn-rich biomass is easily valorized by the use of powdered leaves as green and highly efficient catalysts in organic chemistry 10 , 13 , 14 , 37 .…”
Section: Introductionmentioning
confidence: 99%